The question of Zion - Rose, Jacqueline (Princeton University Press, 2005)
Zionism was inspired as a movement--one driven by the search for a homeland for the stateless and persecuted Jewish people. Yet it trampled the rights of the Arabs in Palestine. Today it has become so controversial that it defies understanding and trumps reasoned public debate. So argues prominent British writer Jacqueline Rose, who uses her political and psychoanalytic skills in this book to take an unprecedented look at Zionism--one of the most powerful ideologies of modern times. Rose enters the inner world of the movement and asks a new set of questions.